PEMANFAATAN SISTEM PEMBAYARAN ELEKTRONIK UNTUK MENGEFISIENKAN WAKTU MENYELESAIKAN PEKERJAAN DI UNIVERSITAS HKBP NOMMENSEN - Mei Hotma Mariati (Fakultas Ekonomi dan Bisnis, Universitas HKBP Nommensen, 2020)
This study aims to find out the reasons why students are required to submit three copies of proof of payment and the reasons for the Nommensen HKBP University so that it only applies the transfer method via ATM as an electronic payment procedure for students. The results of the research were obtained using the descriptive method that so far students have paid tuition fees through BRI using manual code 034. The foundation cannot receive details of the source of revenue and allocation of cash disbursements, providing an explanation why the foundation requires students to submit 3 photocopies of proof of payment of obligations. (three) sheets. When the payment is due, a very long queue will occur. Including going to the TU to generate payments also has its own obstacles for students. So that the university must switch to a virtual account (VA) because it not only makes the transaction process easier, but also has several benefits that are added value services, such as (1) Can accept payments from all banks. (2) Students do not need to confirm and check payment manually. (3) Funds go to campus accounts instantly on the same day. (4) Mapping of Virtual Account numbers that can be adjusted to the campus (for example: BRI Virtual Account Numbers on the campus of the HKBP Nommensen University, must be adjusted to the Student's NPM). (5) Not using campus deposit slips.